Giant pleomorphic adenoma of the submaxillary gland - Suaya, Hadel; Perrone, Luis; Penco, Enrique P.; La Piedra, Eduardo (Cirugía del Uruguay, 1979)
A patient presented a gigantic pleomorphic adenoma of submandibular gland. A revision of existing bibliography led to the conclusion that elective surgical therapy is total submaxillectümy, which has very low rate of recurrency. Malignancy of this type of tumor is very high due to its prolongued evolution and size.